PEMIKIRAN DAN KONTRIBUSI TOKOH EKONOMI ISLAM KLASIK DAN KONTEMPORER - Ahmad Maulidizen (deliberatif, 2017)
Islamic economics is a science that combines economics with the principle of Sharia. The development of Islamic economic thought has begun from the time of the Prophet Muhammad. In writing this article aims to find out the economic scholars of Islam and their contribution in its development. The author distributes Islamic economic scholars in two categories Classical and Contemporary. In the classical Islamic economic scholars include; Zayd ibn ‘Alī, Abū Ḥanīfa, Abū Yūsuf, al-Ghazālī, Ibn Taimiyah, Ibn Khladun, Ibn Qayyim, Shah Wali Allāh al-Naḍwī, Muhammad Abduh and Muhammad Iqbal. When Contemporary Islamic economic scholars are distributed in 3 categories, Iqtiṣādunā (Baqir al-Sadr), Mainstream (Muhammad Abdul Mannan, Nejatullah Siddiqi, Syed Nawab Heider Naqvi and Monzer Kahf), and Alternative (Timur Kuran). Abstrak: Ekonomi Islam merupakan ilmu pengetahuan yang menggabungkan antara ilmu ekonomi dengan prinsip ajaran Syariah. Perkembangan pemikiran dan ilmu ekonomi Islam sudah bermula dari zaman Rasulullah SAW, Sahabat sampai saat ini. Dalam penulisan artikel ini bertujuan untuk mengetahui tokoh ekonomi Islam dan kontribusi mereka dalam pengembangannya. Penulis membagikan tokoh ekonomi Islam dalam dua kategori Klasik dan Kontemporer. Dalam tokoh ekonomi Islam Klasik, yaitu Zaid bin ʻAlī, Abū Ḥanīfah, Abū Yūsuf, al-Ghazālī, Ibn Taimiyah, Ibn Khladun dan Ibn Qayyim, Shah Wali Allāh al-Naḍwī, Muhammad Abduh dan Muhammad Iqbal. Manakala kategori tokoh ekonomi Islam Kontemporer dibagikan dalam 3 Kategori, Aliran Iqtisaduna (Baqir al-Sadr), Aliran Mainstream ( Muhammad Abdul Mannan, Nejatullah Siddiqi, Syed Nawab Heider Naqvi dan Monzer Kahf), dan aliran Alternatif (Timur Kuran).